Navigating professional identity: A case study of Indonesian EFL non-certified teachers - Ismahani , Siti; Hz, Benni Ichsanda Rahman; Nuranisah, Nuranisah; Supiyandi, Supiyandi (Indonesian Research Journal in Education |IRJE|, 2025)
The Indonesian government has enhanced educational quality and teacher professionalism via teacher certification. This research investigates the professional identity of Indonesian EFL (English as a Foreign Language) teachers, who have not been certified, and how they perceive their teaching career and professionalism. This research employs a qualitative case study design to explore the reflective practices of ten teachers who do not possess certification (or have not undergone a certification program). The data collection involved two primary methods: a modified questionnaire comprising six aspects of teacher professional identity and semi-structured interviews. The research findings suggest a tough professional identity beyond formal credentials, particularly the satisfaction and fulfilment of teachers without certification. Collaborative initiatives between the government, educational institutions, and relevant stakeholders are suggested to create a more conducive and rewarding teacher environment.